PROGNOSIS OF RETENTION AND ABNORMAL POSITION OF CANINES - S.I. Doroshenko; O.A. Kaniura; K.V. Storozhenko; S.V. Irkha; D.O. Marchenko; Kh.M. Demianchuk (Український стоматологічний альманах, 2020)
Canines play an important role in the act of chewing and especially in the aesthetics of the face when you smile. They also serve as a guide to the movements of the mandible “canine management” and they are more resistant to carious lesions.